2012
DOI: 10.1038/oby.2011.384
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Increasing BMI on Insulin Sensitivity and Secretion in Normotolerant Men and Women of a Wide Age Span

Abstract: The impact of sex and age on glucose metabolism in the development of overweight/obesity is a matter of debate. We hypothesized that insulin sensitivity (IS) and beta-cell function (BF) in a normal white population will differ between males and females and aimed to evaluate the possible effects of BMI and age on metabolic parameters of both sexes. This study is a cross-sectional analysis of the general community. IS was measured with quantitative insulin sensitivity check index (QUICKI) and oral glucose insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 45 publications
10
59
1
2
Order By: Relevance
“…However, it was shown that in males, diabetes is diagnosed at a lower BMI than in females (26). Males are more insulin resistant and have more visceral and liver fat, which can contribute to their higher diabetes risk (27)(28)(29). These findings could partly explain the higher prevalence of diabetes seen in middle-aged and elderly men (30).…”
Section: Literacy (Si Text)mentioning
confidence: 54%
“…However, it was shown that in males, diabetes is diagnosed at a lower BMI than in females (26). Males are more insulin resistant and have more visceral and liver fat, which can contribute to their higher diabetes risk (27)(28)(29). These findings could partly explain the higher prevalence of diabetes seen in middle-aged and elderly men (30).…”
Section: Literacy (Si Text)mentioning
confidence: 54%
“…When compared with men, women with normal glucose tolerance have been found to be more insulin-sensitive and have better -cell function; however, greater postmenopausal metabolic deterioration has been observed [1,2]. Gender-related differences have been measured using oral glucose tolerance testing, showing that in prediabetic states, women have higher rates of impaired glucose tolerance, whereas the rates of impaired fasting glucose are higher in men [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Use of participants' data for research purposes has been approved by the Hospital Management Committee. Part of the data were already included in previous studies [9,10].…”
Section: Patients and Measurementsmentioning
confidence: 99%
“…From fasting samples, HbA1c was measured by the HA-8140 analyser (Menarini Diagnostics, Italy). Triglycerides, total cholesterol and low-and high-density lipoprotein cholesterol (LDL-C, HDL-C) were determined as previously described [9].…”
Section: Patients and Measurementsmentioning
confidence: 99%